2012
DOI: 10.1007/s11033-012-2369-2
|View full text |Cite
|
Sign up to set email alerts
|

DNA damage and repair in Fuchs endothelial corneal dystrophy

Abstract: Fuchs endothelial corneal dystrophy (FECD) is a slowly progressive eye disease leading to blindness, mostly affecting people above 40 years old. The only known method of curing FECD is corneal transplantation. The disease is characterized by the presence of extracellular deposits called “cornea guttata”, apoptosis of corneal endothelial cells, dysfunction of Descement’s membrane and corneal edema. Oxidative stress is suggested to play a role in FECD pathogenesis. Reactive oxygen species produced during the str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
21
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 26 publications
0
21
0
Order By: Relevance
“…Increased oxidative stress in FECD cornea may contribute to endothelial oxidative DNA damage, morphological modification and apoptosis. We showed that FECD patients displayed greater levels of oxidative DNA lesions compared with age- and sex-matched controls [76]. It was also shown that the level of 8-hydroxy-2′-deoxyguanosine, a marker of oxidative DNA damage, was increased in FECD endothelium [13].…”
Section: Oxidative Stress In the Pathogenesis Of Fuchs Endothelialmentioning
confidence: 99%
“…Increased oxidative stress in FECD cornea may contribute to endothelial oxidative DNA damage, morphological modification and apoptosis. We showed that FECD patients displayed greater levels of oxidative DNA lesions compared with age- and sex-matched controls [76]. It was also shown that the level of 8-hydroxy-2′-deoxyguanosine, a marker of oxidative DNA damage, was increased in FECD endothelium [13].…”
Section: Oxidative Stress In the Pathogenesis Of Fuchs Endothelialmentioning
confidence: 99%
“…44 Interestingly, several authors have found evidence of increased apoptosis having a role in endothelial cell loss, as observed in FECD. 46,47 Furthermore, it was shown that the defense mechanism of FECD endothelium against oxidative stress-induced damage is impaired when compared with normal cells, 39,45,48,49 which is supported by the observed significant higher levels of (baseline) oxidative stressinduced damage, 43,45,48 and changes in endothelial cell morphology characteristic for oxidative stress. 50 These data suggest that chronic oxidative stress contributes to the pathophysiology of FECD, and that the decreased defense system renders FECD endothelial cells even more susceptible to oxidative stress-induced damage than normal cells already are.…”
Section: Pathophysiology Of Fecdmentioning
confidence: 91%
“…[40][41][42] Corneal endothelial cells are thought to be especially vulnerable to oxidative stress-induced damage because they do not proliferate and have a high level of metabolic activity owing to their pump function. 39,43 Fortunately, these cells have several defense mechanisms against the detrimental effects of oxidative stress, 44,45 thereby reducing damage and promoting cell survival. However, if oxidative stress persists, the defense mechanisms fail, thereby allowing the cell to accumulate damage.…”
Section: Pathophysiology Of Fecdmentioning
confidence: 99%
“…Fuchs endothelial corneal dystrophy (FECD) is a slowly progressive eye disease leading to corneal vision loss, mostly affecting people above 40 years old (Czarny et al, 2013). The only definitive treatment of FECD is corneal transplantation (Czarny et al, 2013; Rose et al, 2009).…”
mentioning
confidence: 99%
“…The only definitive treatment of FECD is corneal transplantation (Czarny et al, 2013; Rose et al, 2009). Endoplasmic reticulum (ER) and oxidative stress contribute to the pathogenesis of FECD (Azizi et al, 2011; Engler et al, 2010).…”
mentioning
confidence: 99%